2012
DOI: 10.1111/j.1469-7580.2012.01474.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional and molecular analysis of the arterial pole of the developing human heart

Abstract: Labeling experiments in chicken and mouse embryos have revealed important roles for different cell lineages in the development of the cardiac arterial pole. These data can only fully be exploited when integrated into the continuously changing morphological context and compared with the patterns of gene expression. As yet, studies on the formation of separate ventricular outlets and arterial trunks in the human heart are exclusively based on histologically stained sections. So as to expand these studies, we per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
104
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(110 citation statements)
references
References 33 publications
5
104
0
1
Order By: Relevance
“…In contrast, the distal outflow tract (dOFT) cushion mesenchyme is largely derived from invading cardiac neural crest cells (NCCs) (Kirby et al 1983; Waldo et al 1998; Jiang et al 2000). Additional cell populations, possibly of second heart field (SHF) origin, may contribute additional mesenchyme to the OFT cushions (Engleka et al 2012; Sizarov et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the distal outflow tract (dOFT) cushion mesenchyme is largely derived from invading cardiac neural crest cells (NCCs) (Kirby et al 1983; Waldo et al 1998; Jiang et al 2000). Additional cell populations, possibly of second heart field (SHF) origin, may contribute additional mesenchyme to the OFT cushions (Engleka et al 2012; Sizarov et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Although significant progress has been made toward elucidating the pathways that drive cardiomyocyte (CM) lineages (reviewed in 1 ), relatively less is known about the origins of the distinct endothelial cell (EC) lineages that constitute the coronary arterial, venous and endocardial compartments of the heart. Cumulative studies from the zebrafish 2,3 , chick 4,5 , mouse 6,7,8 and human 9 models have revealed a heterogeneous origin of the endothelial lineages in the heart, and have recently indicated that a subset of these ECs are derived from a distinct origin of multipotent heart progenitors located in various specific regions of the early heart field 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of OFT cushion morphogenesis, size and location remains poorly understood at the molecular level. Certain SHF populations, including those identified by Sizarov et al (Sizarov et al, 2012) and abnormal in morphology and Smad1/5/8 phosphorylation in our models, might play a role in the maintenance of separate nascent truncal lumens close to the OFT wall, perhaps via effects on OFT cushion morphogenesis. As many endocardial /endothelial cells are also recombined by Mef2c[AHF]-Cre , their behavior and signaling may also contribute, especially as cushion shape regulation is sensitive to flow(Colvee and Hurle, 1983; Manner et al, 1993) which might be expected to be abnormal from at least E9 as the right ventricle is abnormally small.…”
Section: Discussionmentioning
confidence: 50%